A Case of Cryptorchidism with Ipsilateral Congenital Unilateral Absence of the Vas Deferens and Contralateral Renal Agenesis - Young Dong Yu; Young Kwon Hong (Case Reports in Urology)
Introduction and Aims. Congenital absence of the vas deferens is an uncommon anomaly and this clinical condition is responsible for up to 1-2% of male infertility. It can be either unilateral or bilateral and the associated anomalies include cryptorchidism, seminal vesicles and ejaculatory ducts anomalies, and renal anomalies such as renal agenesis. We hereby present a case of congenital unilateral absence of vas deferens, which was found incidentally during an evaluation of undescended testis in a patient with ipsilateral renal agenesis. Case Presentation. A 10-month-old boy was referred to the urology clinic with an undescended right testis. Preoperative abdominal ultrasonography showed agenesis of the right kidney and the absence of right vas deferens and epididymis was confirmed during laparoscopic orchiectomy performed due to short right spermatic cord. There were no other concomitant anomalies of the genitourinary system observed in evaluation. Conclusion. Congenital unilateral absence of the vas deferens with cryptorchidism and renal agenesis is a rare diagnostic entity. Cryptorchidism or absent vas deferens found incidentally should lead the physician to evaluate the status of the contralateral vas deferens and conduct a renal tract ultrasound study.